Alzheimer's disease brain-derived amyloid-ß-mediated inhibition of LTP In Vivo is prevented by immunotargeting cellular prion protein - ROWAN, MICHAEL; KLYUBIN, IGOR (My University, 2011)
Synthetic amyloid- protein (A ) oligomers bind with high affinity to cellular prion protein (PrPC), but the role of this interaction in mediating the disruption of synaptic plasticity by such soluble A in vitro is controversial. Here we report that intracerebroventricular injection of A -containing aqueous extracts of Alzheimer?s disease (AD) brain robustly inhibits long-term potentiation (LTP) without significantly affecting baseline excitatory synaptic transmission in the rat hippocampus in vivo. Moreover, the disruption of LTP was abrogated by immunodepletionofA . Importantly, intracerebroventricular administration of antigen-binding antibody fragment D13, directed to a putative A -binding site on PrPC, prevented the inhibition of LTP by AD brain-derived A . In contrast, R1, a Fab directed to the C terminus of PrPC, a regionnotimplicatedinbindingofA ,didnotsignificantly affect theA -mediatedinhibition ofLTP.These data support the pathophysiological significance of SDS-stable A dimer and the role of PrPC in mediating synaptic plasticity disruption by soluble A .
PUBLISHED
Keywords: Alzheimer?s disease; Ageing; Immunology, Inflammation & Infection; Neuroscience